Comparative study on open air burnt low- and high-carbon rice husk ash as partial cement replacement in cement block production. (September 2017) - Mayooran, Selvaraja; Ragavan, Singarajah; Sathiparan, Navaratnarajah
Abstract: This study analyzes the feasibility of using high-carbon content rice husk ash waste generated from open air burning of rice husk, as secondary raw materials in the manufacture of cement blocks. Solid masonry blocks having the size of 215 mm × 105 mm × 65 mm, were cast with the mix proportion of 1:5 cement and sand. Blocks were manufactured with two types of rice husk ash (RHA); low-carbon content RHA and high-carbon content RHA. Cement blocks, at four different RHA replacement levels of 5%, 10%, 15% and 20% were prepared for low and high-carbon RHA as partial cement replacement. Testing was included for workability (water/binder ratio and setting time), strength (compressive, flexural bending and splitting tensile) and durability (water absorption, sorption, acid attack resistance and alkaline attack resistance). Results from this test results indicate that the workability, mechanical and durability characteristics of low-carbon RHA cement blocks slightly better than that of high-carbon RHA cement blocks. However, both RHA replacement cement blocks satisfy the limit recommended by standards. Even, high-carbon RHA replacement cement block does not vastly improve the strength or durability properties, the economic and environmental benefits encourage to use high-carbon RHA in cement block production.